Tradisi Merejung sebagai Media Komunikasi Budaya Suku Serawai - Retno Dwi Putri; Mas Agus Firmansyah (STAI Bumi Silampari, 2026)
This study aims to identify the forms of cultural communication messages contained in the merejung tradition of the Serawai ethnic community in Kepahiang Regency. The merejung tradition is a form of oral literature that has been passed down from generation to generation and is commonly performed in traditional ceremonies, particularly during wedding processions. In addition to functioning as entertainment or an artistic performance, merejung also serves as a medium of cultural communication that conveys social values, moral messages, and cultural identity to the community. However, along with the development of modern times, public understanding especially among the younger generation of the meaning and function of merejung has begun to decline. Therefore, scientific research is needed to reveal the cultural messages embedded within this tradition. This research uses a qualitative descriptive method with an ethnography of communication approach within a constructivist paradigm. Data were collected through observation, in-depth interviews, and documentation involving perrejung (rejung performers), traditional leaders, and members of the Serawai community. Data analysis employed James W. Carey’s ritual communication theory. The results show that the merejung tradition contains three main forms of cultural communication messages: social messages, moral messages, and cultural identity messages that function to strengthen social relationships, provide life advice, and maintain the cultural identity of the Serawai community.